The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1371/journal.pone.0118502
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Responses of Fishes across Multiple Reserves within a Network of Marine Protected Areas in Temperate Waters

Abstract: Meta-analyses of field studies have shown that biomass, density, species richness, and size of organisms protected by no-take marine reserves generally increase over time. The magnitude and timing of changes in these response variables, however, vary greatly and depend upon the taxonomic groups protected, size and type of reserve, oceanographic regime, and time since the reserve was implemented. We conducted collaborative, fishery-independent surveys of fishes for seven years in and near newly created marine p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
73
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 46 publications
(69 reference statements)
5
73
3
Order By: Relevance
“…To put that amount in perspective, the San Francisco Bay covers ∼1,100 km 2 , drains 40% of the state of California (26,27), and receives an estimated annual load of 8.0 kg MeHg from external sources such as rivers and point source discharges (25). Conversely, the Año Nuevo State Marine Conservation Area covers only 26.4 km 2 (28), indicating that the magnitude of annual inputs from pinniped colonization constitutes a relevant, previously unaccounted for, source of MeHg to that marine reserve.…”
Section: Discussionmentioning
confidence: 99%
“…To put that amount in perspective, the San Francisco Bay covers ∼1,100 km 2 , drains 40% of the state of California (26,27), and receives an estimated annual load of 8.0 kg MeHg from external sources such as rivers and point source discharges (25). Conversely, the Año Nuevo State Marine Conservation Area covers only 26.4 km 2 (28), indicating that the magnitude of annual inputs from pinniped colonization constitutes a relevant, previously unaccounted for, source of MeHg to that marine reserve.…”
Section: Discussionmentioning
confidence: 99%
“…The much longer generation time for these species as well as the sporadic recruitment success of rockfish, implies that it will take longer than 3-7 years for reserve effects to develop as a result of increased growth and reproductive output of these species in RCAs. Similarly, Starr et al (2015) found strong reserve effects in an MPA that had been closed since 1973 but not in newer reserves in California that were sampled within the first 7 years of protection. They projected that MPAs in Central California may take 20 years or more to show significant changes in response variables (Starr et al, 2015).…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, Starr et al (2015) found strong reserve effects in an MPA that had been closed since 1973 but not in newer reserves in California that were sampled within the first 7 years of protection. They projected that MPAs in Central California may take 20 years or more to show significant changes in response variables (Starr et al, 2015). Most rockfishes distributed along the continental slope did not show a greater proportion of large fish in closed areas of a large RCA in the US, unlike other species with shorter lifespans (Keller et al, 2014).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…For example, hook-and-line gear is used to sample rocky reefs that are home to many commercially and recreationally important species, as trawl gear would snag in these complex, hard-bottom habitats. Fishery-independent hook-and-line surveys (hereafter "hook and line" refers to pole-and-line gear specifically) have expanded in recent years in the nearshore waters of the northeastern Pacific Ocean both to assess reef fish abundance (Wendt and Starr 2009;Harms et al 2010) and to monitor marine reserve performance (Haggarty and King 2006;Yochum et al 2011;Huntington et al 2014;Starr et al 2015). The numbers of marine reserves are growing in both California, where 124 marine managed areas were implemented between 2007 and 2013 (Kirlin et al 2013), and Oregon, where 13 marine managed areas were implemented between 2012 and 2016.…”
mentioning
confidence: 99%